Maternal Mortality in the General Hospital of Arequipa - Lozada Stanbury, B. (2015)
A study of the experience of seven years at the "Hospital General de Arequipa", Teaching Unit of the School of Medicine of Arequipa, reveals an over all incidence of maternal mortality of 1.8 per thousand live births and 1.46% if all obstetric cases are considered (30,726). There is a definite tendency for improvement with maternal mortality descending to 1.16% live births in 1967. The causes of death in order of importance are infection (33%) toxemia (24%) and hemorrhage (15%). The high incidence of maternal mortality is related to socio-economic factors and the inadequate provision of health care at the prenatal stage.